Consumer ethnocentrism, market mavenism and social network analysis. Issue 3 (August 2018) - Cheah, Isaac; Shimul, Anwar Sadat
Highlights: The validation of the CETSCALE to be used by multinational firms with regards to the segmentation of markets and integrated marketing communications in an Australian context. Australian consumers to have typically low levels of ethnocentrism and is a reflection of the countries dependency on imported products. Positive results in regards to the management of foreign brands within the Australian marketplace. Exploration of MMs within social placement provided some interesting results concerning maven clustering and the closeness of mavens to other social actors. The incorporation of valued relations within a complete network would allow for thorough and accurate social analysis of MMs. Abstract: This study investigates the tendency of consumer ethnocentrism, the role of market mavenism and interactions between these two constructs within a social structure. A total of 215 responses were collected online using the snowballing technique. This study finds that younger consumers are less ethnocentric but demonstrate more mavenism than their counterparts. The social network analysis shows that within the 2-clique, the market mavens outnumbered the non-mavens. This paper provides a holistic view by incorporating the relationship among three concepts with six-degrees-of-separation theory, adding new insights into the constructs which was not previously addressed within the literature. Chinese Abstract: 本研究调查了消费者种族中心主义倾向, 市场专家主义的作用以及这两个概念在社会结构中的相互作用. 通过滚雪球技术在线收集了215份答卷. 本研究发现, 年轻消费者不太以种族为中心, 但比同辈表现出更强烈的行动主义. 社交网络分析显示, 在两派内部, 市场专家主义者 人数超过了非专家主义者. 本文通过将三个概念之间的关系与六度分离理论结合起来, 提供了整体性的观点, 为文献中以前未涉及的构念增加了新的见解.